Physical training performance evaluation via pc based monitoring and database system - Fam Deng Fong (2023)
The aim of the project is to develop a Visual Basic (VB) program to analyze athletes' training data and display training performance on graph for future reference. The training data will be transmitted by a programmable logic controller (PLC) to PC through RS323.